Existence results for strong mixed vector equilibrium problem for multivalued mappings - Kilicman, Adem; Ahmad, Rais; Rahaman, Mijanur (Hindawi Publishing Corporation, 2014)
We consider a strong mixed vector equilibrium problem in topological vector spaces. Using generalized Fan-Browder fixed point theorem (Takahashi 1976) and generalized pseudomonotonicity for multivalued mappings, we provide some existence results for strong mixed vector equilibrium problem without using KKM-Fan theorem. The results in this paper generalize, improve, extend, and unify some existence results in the literature. Some special cases are discussed and an example is constructed.